Investments of uncertain cost - Pindyck, Robert S. (Journal of Financial Economics, 1993)
This paper examines irreversible investment decisions when projects take time to complete and are subject to two types of cost uncertainty. The first is technical uncertainty, i.e., uncertainty over the physical difficulty of completing a project, which is only resolved as the investment proceeds. The second is input cost uncertainty, i.e., uncertainty over the prices of construction inputs or over government regulations affecting construction costs, which is external to the firm. These two types of uncertainty have very different effects on the investment decision. A simple investment rule is derived that maximizes firm value, and is used to analyze the decision to start or continue building a nuclear power plant during the 1980s.